Cellular vaccination of MLH1−/− mice – an immunotherapeutic proof of concept study. (4th March 2018) - Maletzki, Claudia; Gladbach, Yvonne Saara; Hamed, Mohamed; Fuellen, Georg; Semmler, Marie-Luise; Stenzel, Jan; Linnebacher, Michael
ABSTRACT: Mismatch-repair deficiency (MMR-D) is closely linked to hypermutation and accordingly, high immunogenicity. MMR-D-related tumors thus constitute ideal vaccination targets for both therapeutic and prophylactic approaches. Herein, the prophylactic and therapeutic impact of a cellular vaccine on tumor growth and tumor-immune microenvironment was studied in a murine MLH1 −/− knockout mouse model. Prophylactic application of the lysate (+/− CpG ODN 1826) delayed tumor development, accompanied by increased levels of circulating T cell numbers. Therapeutic application of the vaccine prolonged overall survival (median time: 11.5 (lysate) and 12 weeks (lysate + CpG ODN) vs. 3 weeks (control group), respectively) along with reduced tumor burden, as confirmed by PET/CT imaging and immune stimulation (increased CD3 + CD8 + T – and NK cell numbers, reduced levels of TIM-3 + cells in both treatment groups). Coding microsatellite analysis of MMR-D-related target genes revealed increased mutational load upon vaccination (total mutation frequency within 28 genes: 28.6% vaccine groups vs. 14.9% control group, respectively). Reactive immune cells recognized autologous tumor cells, but also NK cells target YAC-1 in IFNγ ELISpot and, even more importantly, in functional kill assays. Assessment of tumor microenvironment revealed infiltration of CD8 + T-cells and granulocytes, but also upregulation of immune checkpoint molecules (LAG-3, PD-L1). The present study is the first reporting in vivo results on a therapeutic cellular MMR-D vaccine. Vaccination-induced prolonged survival was achieved in a clinically-relevant mouse model for MMR-D-related diseases by long-term impairment of tumor growth and this could be attributed to re-activated immune responses.